Cyclic uniaxial compression of human stem cells seeded on a bone biomimetic nanocomposite decreases anti-osteogenic commitment evoked by shear stress. (July 2018) - Baumgartner, Walter; Schneider, Isabelle; Hess, Samuel C.; Stark, Wendelin J.; Märsmann, Sonja; Brunelli, Marzia; Calcagni, Maurizio; Cinelli, Paolo; Buschmann, Johanna
Abstract: Objective: Chemical supplementation of culture media to induce differentiation of adult stem cells seeded on a scaffold may mask other differentiation triggers such as scaffold stiffness, chemical composition or mechanical stimulation. However, stem cells can be differentiated towards osteoblasts without any supplementation given an appropriate osteogenic scaffold and an adequate mechanical stimulation. Materials and Methods: Electrospun meshes of poly-lactic-co-glycolic acid and amorphous calcium phosphate nanoparticles (PLGA/aCaP) in a weight ratio of 60:40 were seeded with human adipose-derived stem cells (ASCs) and cultured in DMEM. After two weeks of static cultivation, they were either further cultivated statically for another two weeks (group 1), or placed in a Bose® bioreactor with a flow rate per area of 0.16 mL cm −2 min 1 (group 2). Furthermore, group 3 was also cultivated under perfusion, however, with an additional uniaxial cyclic compression. Stiffness of the scaffolds was assessed as a function of time. After a total of four weeks, minimum stem cell criteria markers as well as typical markers for osteogenesis, endothelial cell differentiation, adipogenesis and chondrogenesis were analyzed by quantitative real-time PCR, cell distribution within the scaffolds by histology and protein expression by immunohistochemistry. Results: Dynamic conditions (perfusion ± uniaxial cyclic compression) significantly upregulated gene and protein expression of PPAR-γ-2 compared to static cultivation, while osteogenic markers were slightly downregulated. However, the compression in the perfusion bioreactor favored osteogenesis compared to mere perfusion as indicated by upregulation of ALP, Runx2 and collagen I. This behavior was not only attributed to the compressive load, but also to the significant increase in stiffness of the scaffold. Furthermore, CD105 was significantly upregulated under compression. Conclusions: Although an osteogenic electrospun composite material with an organic (PLGA) and an inorganic phase (aCaP nanoparticles) was used as scaffold, the dynamic cultivation as realized by either perfusion alone or an additional compression did not upregulate typical osteogenic genes when compared to static cultivation. In contrast, there was a significant upregulation of the adipogenic gene PPAR-γ-2. However, this anti-osteogenic starting point evoked by mere perfusion was partially reversed by an additional compression. Our findings exemplify that bone tissue engineering using adult stem cells should consider any other differentiations that may be triggered and overwhelm the desired differentiation, although experimental conditions theoretically provide cues to achieve it – like an osteogenic scaffold and mechanical stimulation.